New Molecular Aspects of Cardiac Arrest; Promoting Cardiopulmonary Resuscitation Approaches - Mona Zamanian-Azodi; Mostafa Rezaei-Tavirani; Mohammad Rostami-Nejad; Fatemeh Tajik-Rostami (Emergency, 2018)
Introduction: Cardiopulmonary resuscitation (CPR) is a method to improve survival of patients with cardiac arrest. This study aimed to identify the key genes affected five minutes after cardiac arrest, hoping to elevate the efficacy of CPR.